Numerical Modelling Of Glass Fibre Reinforced Polymer (Gfrp) Tube Subjected To Torsion - Syamsir, Agusril; Binti Mohd Hafiz, Nurul Amira (Jurnal Rekayasa Sipil (JRS-Unand), 2021)
Glass Fibre Reinforced Polymer (GFRP) tubes have been used widely as cross arm of electric transmission towers to replaced old wooden cross arms. Cross arm is a part of transmission tower which is required to support conductors or electrical cables. Due to nature of assembly of these GFRP tubes, it will induce torsional force to the individual GFRP tubes of cross arm. The importance of torsional effect to the cross arm has encouraged researcher to study on torsional strength of the single tube itself in order to support a complete set cross arm. In this paper, the performance of glass fiber-reinforced polymer (GFRP) tubes under statically torsional loads was studied numerically. The specimens’ ultimate twisting angle and strain were studied through tests for validation of the numerical model. Explicit solver of ANSYS was chosen and simulation results matched experiment results well with 4 % different. There are six model were simulated and analyzed in this research. It is concluded that model 4 shown the highest ultimate strains as well as twisting angle while model 3 has the lowest ultimate strains and twisting angle. The presence of fiber orientation of 90o in model 4 has contributed to the torsional capacity of the tubes.